2016
DOI: 10.7895/ijadr.v5i2.217
|View full text |Cite
|
Sign up to set email alerts
|

Replication of psychometric properties and predictive validity of the Important People Drug and Alcohol Interview

Abstract: Aims: Social support is a predictor of alcohol and drug use. The Important People Drug and Alcohol (IPDA) interview and its predecessor, the Important People and Activities (IPA) measure, have been used to demonstrate this predictive relationship. The purpose of this study was to replicate the findings from Zywiak et al. (2009) in a sample of probationers with substance use disorders.Design: Analyses mirrored those done previously to replicate the associations between social networks and substance use. The IPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The IPDA is a revised version of the Important People and Activities interview (Beattie & Longabaugh, 1999) that asks participants to list members in their social network, as well as the importance, supportiveness, drinking and drug use status, and support for substance use treatment of each network member (Owens & Zywiak, in press; Zywiak et al, 2009). Longabaugh et al (1998) found that the earlier version, the Important People Interview, had high 2-3 day test-retest reliability ( r = 0.95).…”
Section: Methodsmentioning
confidence: 99%
“…The IPDA is a revised version of the Important People and Activities interview (Beattie & Longabaugh, 1999) that asks participants to list members in their social network, as well as the importance, supportiveness, drinking and drug use status, and support for substance use treatment of each network member (Owens & Zywiak, in press; Zywiak et al, 2009). Longabaugh et al (1998) found that the earlier version, the Important People Interview, had high 2-3 day test-retest reliability ( r = 0.95).…”
Section: Methodsmentioning
confidence: 99%
“…A number of social network indices can be derived from the IPDA and have been previously validated (Owens & Zywiak, 2016;Zywiak et al, 2009). We calculated nine social network characteristics: 1) number of people in the social network, 2) number of people in daily contact with the participant, 3) the average importance rating of the four social network members rated the highest, 4) number of alcohol users in social network, 5) number of drug users in social network, 6) network's AOD involvement, 7) general social support, 8) treatment support, and 9) support for AOD use.…”
Section: Treatment Termination and Progressmentioning
confidence: 99%
“…The structure and complexity of social networks of individuals with SUD have so far been largely studied through self-report. The Important (Owens & Zywiak, 2016;Zywiak et al, 2009) and, by far, the most commonly used methods of social network evaluation in the SUD realm (Stone, Jason, Light, & Stevens, 2016). For example, IPA and IPI were included in the most prominent large-scale studies on the treatment of alcohol problems, projects MATCH (Zywiak, Longabaugh, & Wirtz, 2002) and COMBINE (Longabaugh, Philip, William, & Stephanie, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation